The future of well-care for adolescents in Poland. More questions than answers - Rybicka-Kramarz, Anika; Henzler, Michał; Walczak, Agata; Kucharski, Bartłomiej; Nitsch-Osuch, Aneta; Bogdan, Magdalena (Family Medicine & Primary Care Review, 2023)
Department of Social Medicine and Public Health, Medical University of Warsaw, Warsaw, Poland This year marks the 20th anniversary of the publication by the Institute of Mother and Child in Warsaw of a document establishing the Polish standards for preventive health care of school-age children and adolescents by general practitioners, which are still in force today. Since then, their health status and the health risk factors have changed. Polish society and its expectations of health care are also different. The Polish economy has grown, and the proportion of the public budget spent on health care has increased. The current system of preventive health care for young people seems to be facing a problem. Over the past decade, the percentage of children and adolescents attending preventive medical visits in Poland has decreased by approximately 30%. During well-care visits, doctors commonly avoid selected physical examinations and sensitive topics, such as sexuality or mental health. It appears that most young people visit doctors only because they falsely believe that check-up visits are mandatory and usually rate the experience negatively. The co-authors of this paper conclude that there is a need for a broad debate on the Polish standards of preventive health care for adolescents and their possible reform, which would lead to their adaptation to the challenges of modern times and the opportunities offered by the progress of medical science and technology. The selection of topics is subjective and certainly does not cover all aspects requiring attention. The authors’ intention is to contribute to further discussion rather than to provide a basis for conclusions or postulates.